Pengaruh Implementasi Standar Akuntansi Pemerintah Berbasis Akrual dan Sistem Pengendalian Intern terhadap Kinerja Keuangan Pemerintah Kota Lhokseumawe - Putri Miranda; Ikhyanuddin Ikhyanuddin; Indrayani Indrayani; Nurhasanah Nurhasanah (Yayasan Pendidikan Penelitian Pengabdian Algero, 2022)
This study aims to determine the effect of the implementation of accrual-based government accounting standards and internal control systems on the financial performance of the Lhokseumawe City government, either partially or simultaneously. This type of research is descriptive quantitative research that emphasizes causal design. The method used for sampling in this study is a non-probability sampling method with a saturated sample type where the entire population is sampled, with as many as 22 Lhokseumawe City Regional Work Units taken 5 respondents to represent each Regional Work Units. The initial research sample amounted to 110 respondents, but there was a realization of the sample so that the total sample was 86 respondents. The data used in this study is primary data with data collection techniques using a questionnaire. The data analysis method in this study used multiple linear regression analysis using SPSS version 26. Tests in this study used validity and reliability tests, classical assumption tests and hypothesis tests. There are 3 classical assumption tests in this study, namely normality test, multicollinearity test, and heteroscedasticity test. Meanwhile, the hypothesis test consists of partial test (t test) and simultaneous test (F test). The test results show that partially, Accrual-Based Government Accounting Standards have a positive and significant effect on Government Financial Performance; and the Internal Control System has a positive and significant effect on the Government's Financial Performance. Simultaneously, Accrual-Based Government Accounting Standards and Internal Control Systems have a significant effect on Government Financial Performance.